Wissenschaft und Ideologie – die liberale Bioethik und der Strukturwandel rassistischer Diskurse - Bogner, A. (Wiener Zeitschrift zur Geschichte der Neuzeit, 2003)
The article deals with the ideological implications of contemporary liberal bioethics. It draws on important works of different utilitarian philosophers. The analysis focuses on the main concepts of “person” or “personal life“, which are appraised as an ideological way of answering the central bioethical question of who’s life is worth to be lived. This way is ideological with regard to the obvious fact that the differentiation between what is called “person” and “human being” respectively is based on a transfiguration of dominant moral concepts in late modernity. Referring to new theories of racism, which recognize the phenomenon “racism” as a process of signification that establishes and legitimizes specific power relations, the article examines homologies between current bioethical discourses and racism. The author suggests that liberal bioethics, which include a discourse of marginalization, can be considered as a modernist form of racism provided that racism implies a specific structure of ideological discourse – and not only a practice of exclusion.